Inappropriate ICD Shocks - When Monitoring Zones Do More Than Monitor - Reinder Evertz, MD; Emilce Trucco, MD (Indian Pacing and Electrophysiology Journal, 2013)
The ventricular tachycardia (VT) monitoring zone in implantable cardioverter defibrillators (ICDs) is usually programmed to detect slow VTs. However, it is not well known whether programming this zone can affect the ICD arrhythmia redetection or confirmation criteria. We report two cases of inappropriate ICD shocks due to the programming of a slow VT monitoring zone in the same device model.